Selective etching of injection molded zirconia-toughened alumina: Towards osseointegrated and antibacterial ceramic implants. (December 2016) - Flamant, Quentin; Caravaca, Carlos; Meille, Sylvain; Gremillard, Laurent; Chevalier, Jérôme; Biotteau-Deheuvels, Katia; Kuntz, Meinhard; Chandrawati, Rona; Herrmann, Inge K.; Spicer, Christopher D.; Stevens, Molly M.; Anglada, Marc
Graphical abstract: Abstract: Due to their outstanding mechanical properties and excellent biocompatibility, zirconia-toughened alumina (ZTA) ceramics have become the gold standard in orthopedics for the fabrication of ceramic bearing components over the last decade. However, ZTA is bioinert, which hampers its implantation in direct contact with bone. Furthermore, periprosthetic joint infections are now the leading cause of failure for joint arthroplasty prostheses. To address both issues, an improved surface design is required: a controlled micro- and nano-roughness can promote osseointegration and limit bacterial adhesion whereas surface porosity allows loading and delivery of antibacterial compounds. In this work, we developed an integrated strategy aiming to provide both osseointegrative and antibacterial properties to ZTA surfaces. The micro-topography was controlled by injection molding. Meanwhile a novel process involving the selective dissolution of zirconia (selective etching) was used to produce nano-roughness and interconnected nanoporosity. Potential utilization of the porosity for loading and delivery of antibiotic molecules was demonstrated, and the impact of selective etching on mechanical properties and hydrothermal stability was shown to be limited. The combination of injection molding and selective etching thus appears promising for fabricating a new generation of ZTA components implantable in direct contact with bone. Statement of Significance: Zirconia-toughened alumina (ZTA) is the current gold standard for the fabrication of orthopedic ceramic components. In the present work, we propose an innovative strategy to provide both osseointegrative and antibacterial properties to ZTA surfaces: we demonstrate that injection molding allows a flexible design of surface micro-topography and can be combined with selective etching, a novel process that induces nano-roughness and surface interconnected porosity without the need for coating, avoiding reliability issues. These surface modifications have the potential to improve osseointegration. Furthermore, our results show that the porosity can be used for drug delivery and suggest that the etched surface could reduce bacterial adhesion.